How can we know what the public think about administrative data research - Porteous, Carol (International Journal of Population Data Science, 2018)
Background There has, in recent years been much discussion in administrative data research about communicating with the public about the research undertaken, listening to the public and trying to understand public views and questioning whether the public have trust in the work undertaken using publicly collected administrative data. Objectives To explore the role of public engagement in dialogue with attendees to try and address whether we are missing the point and value of public engagement. The views of publics are not homogenous, static and also respond to news headlines and data breaches and we can never know the views of 65 million people across the UK, so why do we worry so much about the views of the public and how can we ever know what publics think? Findings Summarising work undertaken in examining public attitudes and reflections on five years of working in public engagement in administrative data research will explore key questions with the audience including. Is there value in considering the views of the public, and if so what is the value? How is the public constituted in its relationships with academia and do the public play a key position in the role of universities within our society?